A Quick Glance at Digital Watermarking in Medical Images Technique Classification, Requirements, Attacks and Application of Tamper Localization - Syifak Izhar, Hisham; Liew, Siau-Chuin; Jasni, Mohamad Zain (World Academic Publishing, 2013)
Digital watermarking is seen as a necessary and important field to be developed since the attacks and manipulations of digital documents and media are actively done. This paper surveys and reviews some basic theory about digital watermarking, such as the technique classification, requirements and possible attacks nowadays. Since all data in medical images are significantly important, the demand for the authentication is high. Therefore, this paper also focuses on a specific application of digital image watermarking for medical images which is tamper localization.